KEMAMPUAN MENULIS CERPEN SISWA KELAS IV SD KOTA MAGELANG - NFN Sutarsih (Multilingual, 2015)
Writing is a language skills in addition to language skills, namely reading, speaking,and listening. Writing becomes a difficult activity for elementary school studentsbecause they have not technique to put the idea in the form of writing. Therefore, theformulation of the problem in this study were 1) how elementary school students'ability in writing? and 2) any barriers experienced by students in the writing process?In line with the formulation of the problem, the purpose of this study was 1) todescribe the ability of elementary school students in writing and 2) describe thebarriers experienced by students in the writing process. This study used a qualitativedescriptive method. The study population was a whole bouquet of fourth gradestudents in the form of short stories Magelang . The sample was is a short storywritten by fourth grade students Magelang 6 and fourth grade students Magelang 7.Sampling techniques such as interviews and observation techniques. In addition,researchers conducted tests to assess students' ability to write a short stories. Thisstudy uses data analysis techniques discourse analysis. The results showed that thebiggest obstacles experienced by students is to find an idea and write the first sentencein the beginning of writing. With technical tests, students are able to write essays. Inaddition, the results of the students 'essays featured SD better than the results of thestudents' essays nonunggulan.